Penyusunan Laporan Keuangan Di Umkm - Kusmawati, Kusmawati (Prodi Akuntasi, Fakultas Bisnis dan Akuntansi Unika Musi Charitas, 2022)
Financial statement have benefit for the firm, because give information for planning and decision making. Standart of financial statement for little company are simple. The fact are much little company not make financial statement. The purpose of this research are to know about factors that effect preparing financial statement by little company. The population of this research are little company that be IKM Nusantara community, and metode of sample selection is simple random sampling. This research are used primer of data and questioner are used to collect data. The result of this research are that information of financial statement, customer orientacion, education, and age of company not effect to preparation of financial statement at little company.